Beetroot (Beta vulgaris) Extract: A Potential Therapeutic Agent for Modulating Post-Cholecystectomy Colonic Inflammation? An In Vivo Evidence Review - Mahmudin Ardian Ashadi; Sigit Adi Prasetyo; Yora Nintida (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Cholecystectomy, while a common and effective treatment for symptomatic gallstones, can induce alterations in bile flow and gut microbiota composition, potentially leading to colonic inflammation. Beetroot (Beta vulgaris) extract, rich in betalains, nitrates, and other bioactive compounds, has demonstrated anti-inflammatory and antioxidant properties in various models. This systematic review evaluates the in vivo evidence for the efficacy of beetroot extract in modulating colonic inflammation following cholecystectomy. Methods: A systematic search of PubMed, Scopus, Web of Science, and Embase databases was conducted from January 2013 to May 2024, using keywords related to "beetroot," "Beta vulgaris," "cholecystectomy," "colon," "inflammation," and "in vivo." Studies investigating the effects of beetroot extract on colonic inflammation in animal models post-cholecystectomy were included. Data on inflammatory markers, histological changes, oxidative stress markers, and gut microbiota alterations were extracted. Results: Seven in vivo studies met the inclusion criteria. Beetroot extract administration was associated with significant reductions in colonic levels of pro-inflammatory cytokines (TNF-α, IL-6, IL-1β) in five studies. Data showed an average reduction of TNF-α by 35% (p < 0.01), IL-6 by 28% (p < 0.05), and IL-1β by 42% (p < 0.001) across these five studies. Four studies reported improvements in histological scores of colonic inflammation, indicating reduced tissue damage. Three studies demonstrated a decrease in MPO activity, a marker of neutrophil infiltration, with data showing an average reduction of 25% (p < 0.05). Conclusion: The available in vivo evidence, albeit limited, suggests that beetroot extract possesses significant potential for mitigating colonic inflammation following cholecystectomy. The observed anti-inflammatory effects are likely mediated by a combination of betalain-induced antioxidant and anti-inflammatory actions, nitrate-derived nitric oxide signaling, and modulation of the gut microbiota.